Arginine Metabolism in Myeloid Cells Shapes Innate and Adaptive Immunity - Rodriguez, Paulo C.; Ochoa, Augusto C.; Al-Khami, Amir A. (Frontiers in Immunology, 2017)
Arginine metabolism has been a key catabolic and anabolic process throughout the evolution of the immune response. Accruing evidence indicates that arginine-catabolizing enzymes, mainly nitric oxide synthases and arginases, are closely integrated with the control of immune response under physiological and pathological conditions. Myeloid cells are major players that exploit the regulators of arginine metabolism to mediate diverse, although often opposing, immunological and functional consequences. In this article, we focus on the importance of arginine catabolism by myeloid cells in regulating innate and adaptive immunity. Revisiting this matter could result in novel therapeutic approaches by which the immunoregulatory nodes instructed by arginine metabolism can be targeted.